2018
DOI: 10.1016/j.jvs.2017.07.108
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic endovascular aortic repair migration and aortic elongation differentiated using dual reference point analysis

Abstract: These results highlight the dynamic changes that can occur in the aorta as a natural consequence of age. Employing two landmarks can account for these changes and proves to be an important factor, among others, in the differentiation of aortic elongation from true stent graft migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…2,3 Although aortic morphological changes with aging has been reported, 5 aortic elongation after TEVAR is known to occur as well as a normal aging process. 14 Chen et al 4 have reported that aortic elongation after TEVAR occurs over time, with a median change in aortic length from innominate artery to celiac artery of 1.7 mm/year. However, in our case, BMS migration by approximately half of its length occurred within 1 month postoperatively and is considered to be related to another pathogenesis except for whole aortic elongation with aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Although aortic morphological changes with aging has been reported, 5 aortic elongation after TEVAR is known to occur as well as a normal aging process. 14 Chen et al 4 have reported that aortic elongation after TEVAR occurs over time, with a median change in aortic length from innominate artery to celiac artery of 1.7 mm/year. However, in our case, BMS migration by approximately half of its length occurred within 1 month postoperatively and is considered to be related to another pathogenesis except for whole aortic elongation with aging.…”
Section: Discussionmentioning
confidence: 99%
“…Device migration has been recognized as a serious complication after thoracic endovascular aortic repair (TEVAR) as it may lead to endoleaks, device separation, stent collapse, and branch vessel coverage. 1 Previous studies on device migration have focused on pre-existed aortic morphology (aortic length, diameter, angle, and tortuosity). [1][2][3][4] However, the relationship between device migration and aortic remodeling after TEVAR in aortic dissection has not been highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…2,38,39 However, reported studies have also suggested the loss of fixation and migration will result in increased movement of the graft and fatigue stress on the stent rings. 5,23 Aortic elongation will be more pronounced at the distal end of the thoracic aorta, 40,41 and the morphologic changes in the anatomy will affect the structural integrity of grafts. 2,4 Furthermore, angulation is a well-discussed risk factor for graft migration and a compromised seal.…”
Section: Discussionmentioning
confidence: 99%
“…Migration has been commonly defined as having a movement of more than 5 or 10 mm between the stent graft tip and an anatomical landmark along the aorta [13,24]. If there was elongation of the aortic segment distal to the stent graft and proximal to the distal landmark, such as the celiac artery, the stent graft could be misclassified as migrating cranially [12]. Knowing the elongation is essential for correctly determining stent migration.…”
Section: Discussionmentioning
confidence: 99%
“…Reintervention was performed in 11.5% of type B dissections after TEVAR, for conditions such as stent graft-related complication [9]. While the rate of migration has been reported to be 4% [10], aortic elongation could interfere with the process of deciding whether there was migration of stent graft [11], and elongation could be mis-interpreted as stent graft migration [12].…”
Section: Introductionmentioning
confidence: 99%